Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Kualitas Pelayanan Masyarakat Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lahat - Andayani, Melia (MOTIVASI, 2019)
Purpose - This study was to determine competence and work environment on the quality of community services in the population and civil registration services of the district Lahat.Design/methodology - the number of respondents in this research was 40 responden. From the partial test (t test) competence (X1) t count 4.892> t table 2.023 and significant level 0.000 < 0,05 mean competence a significant effect on the quality of community services in the population and civil registration services of the district Lahat (Y). and the partial test (t test) work environment variabel (X2) t count 3.335 > t table 2.023 and significant level 0.02<0,05 mean work environment a significant effect on the quality of community services in the population and civil registration services of the district Lahat (Y).Findings - From ANOVA test or F test obtained f count 18.442 with probability 0.000 ( P value < ? ) then Ho and Hi received. so competence and work environment together have a significant effect on the quality of community services in the population and civil registration services of the district Lahat (Y).